Approach and Withdrawal Tendencies during Written Word Processing: Effects of Task, Emotional Valence, and Emotional Arousal - Citron, Francesca M. M.; Abugaber, David; Herbert, Cornelia (Frontiers in Psychology, 2016)
The affective dimensions of emotional valence and emotional arousal affect processing of verbal and pictorial stimuli. Traditional emotional theories assume a linear relationship between these dimensions, with valence determining the direction of a behaviour (approach vs. withdrawal) and arousal its intensity or strength. In contrast, according to the valence-arousal conflict theory, both dimensions are interactively related: positive valence and low arousal (PL) are associated with an implicit tendency to approach a stimulus, whereas negative valence and high arousal (NH) are associated with withdrawal. Hence, positive, high-arousal (PH) and negative, low-arousal (NL) stimuli elicit conflicting action tendencies. By extending previous research that used several tasks and methods, the present study investigated whether and how emotional valence and arousal affect subjective approach vs. withdrawal tendencies towards emotional words during two novel tasks. In Study 1, participants had to decide whether they would approach or withdraw from concepts expressed by written words. In Studies 2 and 3 participants had to respond to each word by pressing one of two keys labelled with an arrow pointing upward or downward. Across experiments, positive and negative words, high or low in arousal, were presented. In Study 1 (explicit task), in line with the valence-arousal conflict theory, PH and NL words were responded to more slowly than PL and NH words. In addition, participants decided to approach positive words more often than negative words. In Studies 2 and 3, participants responded faster to positive than negative words, irrespective of their level of arousal. Furthermore, positive words were significantly more often associated with "up" responses than negative words, thus supporting the existence of implicit associations between stimulus valence and response coding (positive is up and negative is down). Hence, in contexts in which participants’ spontaneous responses are based on implicit associations between stimulus valence and response, there is no influence of arousal. In line with the valence-arousal conflict theory arousal seems to affect participants’ approach-withdrawal tendencies only when such tendencies are made explicit by the task, and a minimal degree of processing depth is required.